The telling room : a tale of love, betrayal, revenge, and the world's greatest piece of cheese - Paterniti, Michael (Dial Press, 2013)
In the picturesque village of Guzmán, Spain, in a cave on the edge of town, there is a cramped limestone chamber known as "the telling room." This is where villagers have gathered for centuries to share their stories and secrets--usually accompanied by copious amounts of wine. It was here, in the summer of 2000, that Michael Paterniti found himself listening to a Spanish cheesemaker as he spun an odd and compelling tale about a piece of cheese. Made from an old family recipe, Ambrosio's cheese was reputed to be among the finest in the world, and was said to hold mystical qualities. But then, Ambrosio said, things had gone horribly wrong. Paterniti was hooked. Soon he was fully embroiled, relocating his young family to Guzmán in order to chase the truth about this fairy tale-like place. What he ultimately discovers is nothing like the idyllic fable he first imagined. Instead, he's sucked into the heart of an unfolding mystery, a blood feud that includes accusations of betrayal and theft, death threats, and a murder plot.--From publisher description.